Chronic Exposure to Low Concentration Lead Chloride-Induced Anxiety and Loss of Aggression and Memory in Zebrafish - Bui Thi, Ngoc Hieu (Int J Mol Sci, 2020)
Lead and lead-derived compounds have been extensively utilized in industry, and their chronic toxicity towards aquatic animals has not been thoroughly addressed at a behavioral level. In this study, we assessed the risk of exposure to lead at a waterborne environmental concentration in adult zebrafish by behavioral and biochemical analyses. Nine tests, including three-dimension (3D) locomotion, novel tank exploration, mirror biting, predator avoidance, social interaction, shoaling, circadian rhythm locomotor activity, color preference, and a short-term memory test, were performed to assess the behavior of adult zebrafish after the exposure to 50 ppb PbCl(2) for one month. The brain tissues were dissected and subjected to biochemical assays to measure the relative expression of stress biomarkers and neurotransmitters to elucidate the underlying mechanisms for behavioral alterations. The results of the behavioral tests showed that chronic exposure to lead could elevate the stress and anxiety levels characterized by elevated freezing and reduced exploratory behaviors. The chronic exposure to PbCl(2) at a low concentration also induced a sharp reduction of aggressiveness and short-term memory. However, no significant change was found in predator avoidance, social interaction, shoaling, or color preference. The biochemical assays showed elevated cortisol and reduced serotonin and melatonin levels in the brain, thus, altering the behavior of the PbCl(2)-exposed zebrafish. In general, this study determined the potential ecotoxicity of long-term lead exposure in adult zebrafish through multiple behavioral assessments. The significant findings were that even at a low concentration, long-term exposure to lead could impair the memory and cause a decrease in the aggressiveness and exploratory activities of zebrafish, which may reduce their survival fitness.